Understanding PC hardware - Marcelo, Antoinette R. (Philippines, 2007)
Understanding PC Hardware is a book that explains the components and functions of a personal computer, covering both hardware and system architecture. It details key components like the CPU, RAM, motherboard, storage devices, power supply, and peripheral connections. The book also explores how these components interact, troubleshooting common hardware issues, and upgrading or replacing parts for better performance. Additionally, it provides insights into different types of processors, memory configurations, and expansion slots, helping readers make informed decisions about their PC needs. Overall, it serves as a comprehensive guide for beginners and enthusiasts looking to understand and optimize their computer hardware.
Keywords: Computer science; Computer-trouble shooting